Pendekatan Penilaian Autentik dalam Evaluasi Pembelajaran Pendidikan Agama Islam (PAI): The Authentic Assessment Approach in the Evaluation of Islamic Religious Education (PAI) Learning - Sal Shakhiba Albira Nanda Hanafi; Andis Suha Fadhila; Abdul Bashith (Educan, 2025)
Assessment plays an important role in evaluating student learning progress. The change in the learning paradigm in the Merdeka Curriculum encourages the implementation of assessments that are not only oriented to the final results, but also to the process and character of students. In the context of Islamic Religious Education (PAI), authentic assessment offers a more comprehensive method for assessing students' ability to apply religious teachings in real-life situations. The purpose of this study is to find out the effect of the authentic assessment approach on the effectiveness of Islamic Education learning, especially in assessing aspects of students' spiritual and social attitudes, and conceptual understanding comprehensively. This research uses the library research method, to obtain a theoretical basis and draw relevant conclusions, so as to facilitate the completion of this research by referring to related sources. The results showed that authentic assessment promotes active learning and allows for a more thorough evaluation of students' abilities. The study also found that this approach improved students' understanding and application of Islamic values in their daily lives, while encouraging positive changes in their spiritual and social competencies. In conclusion, the authentic assessment approach is able to provide a more holistic and relevant evaluation picture in PAI learning and support the achievement of educational goals as a whole.